1992
DOI: 10.1038/355728a0
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of HIV-1 infection in chimpanzees by gpl20 V3 domain-specific monoclonal antibody

Abstract: The acquired immunodeficiency syndrome (AIDS) is the late-stage clinical manifestation of long-term persistent infection with the human immunodeficiency virus type 1 (HIV-1). Immune responses directed against the virus and against virus-infected cells during the persistent infection fail to mediate resolution of the infection. As a result, a successful AIDS vaccine must elicit an immune state that will prevent the establishment of the persistent infection following introduction of the virus into the host. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
208
0
3

Year Published

1994
1994
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 472 publications
(217 citation statements)
references
References 15 publications
6
208
0
3
Order By: Relevance
“…Antiviral and protective activities were detected when neutralizing Abs were i.v. administered passively (14,49,59,60,61). These data clearly suggest that systemic Abs can provide protection against mucosal virus exposure, but because IgG or monomeric IgA in serum and plasma will not be actively transported across mucosa, whereas secretory IgA or IgM will, we believe that mucosal IgA Abs could play an important role and also inhibit epithelial HIV transcytosis (21).…”
Section: Figurementioning
confidence: 92%
See 1 more Smart Citation
“…Antiviral and protective activities were detected when neutralizing Abs were i.v. administered passively (14,49,59,60,61). These data clearly suggest that systemic Abs can provide protection against mucosal virus exposure, but because IgG or monomeric IgA in serum and plasma will not be actively transported across mucosa, whereas secretory IgA or IgM will, we believe that mucosal IgA Abs could play an important role and also inhibit epithelial HIV transcytosis (21).…”
Section: Figurementioning
confidence: 92%
“…They compared 862 HIV-1 strains and showed that 90 -97% of the isolates contain the LQAR sequence in the coiled-coil region, whereas the LELDKWAS region showed a more variable mix of 50 -97% conserved amino acids (with amino acids L-LD-W being ÏŸ97% conserved). This combination of epitopes included in a vaccine may provide the conserved epitopes that have been so difficult to find in other regions of the HIV-1 envelope even though highly conserved cross-neutralization Ab-inducing epitopes have been described in the gp120 V3 region aa GPGR (47)(48)(49) and within the CD4-binding region of gp120 (50). Additional evidence suggesting the importance of inducing Abs against these gp41 epitopes is the low frequency of Ab reactivities against these regions in HIV-infected individuals (51).…”
Section: Figurementioning
confidence: 99%
“…An optimal acquired immunodeficiency syndrome (AIDS) vaccine should be able to induce both envelope glycoprotein 120 (gp120)-specific neutralizing antibodies, as well as systemic and mucosal cellular immune responses to human immunodeficiency virus (HIV)-infected cells [1][2][3][4][5][6][7]. Vaccine strategies which elicit potent cytotoxic T cell (CTL) responses lead to reduced virus loads and long-term protection against immunodeficiency disease in macaque challenge studies using simian immunodeficiency virus (SIV) or pathogenic simian-human immunodeficiency virus chimeras (SHIV) [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Fax + 33 88 56 63 03. expensive to maintain in numbers sufficient for experimental research and from the point of view of vaccine development, the SIV-macaque model is less than ideal since the SIV genome is not totally analogous to that of HIV-1, especially at the third hypervariable region (Kirchoff et al, 1994). The ~V3 loop' is likely to be a critical element in a protective immune response (Goudsmit et al, 1988;Javaherian et al, 1990;Emini et al, 1992).…”
Section: Introductionmentioning
confidence: 99%